A new chemistry of sound : the technique of multiphonics as a compositional element for guitar and amplified guitar - Torres, Rita Luzes (2017)
Due to lack of tone colour research on the guitar, the technique of multiphonics was investigated on this instrument. It was part of a strategy of presenting non-guitarist composers with new results from the exploration of unconventional performance techniques. Colour research on the guitar is usually carried out by such composers but these tend to dismiss the instrument. If, enticed by these results, they consider composing for guitar, the research's aim of contributing to the promotion of colour research on this instrument and to the establishment of multiphonics as part of its vocabulary would be fulfilled. The technique of multiphonics consists, like the technique of harmonics, in damping out some of the vibrational modes of the string by lightly touching it at certain locations during or after its excitation (or both). Unlike with the technique of harmonics, the filtering of the vibrational modes is not systematic with respect to mode number, for which it is easier to perceive multiple pitches, of which some may be quite soft. The technique has yet to be absorbed into the guitar's vocabulary, possibly because it only recently received renewed attention. The information that is provided in the recent scientific literature is, however, limited. Moreover, it ignores the influence of the differences that may exist between players/instruments, it does not always take psychoacoustics into account, and it does not explore the amplification of the sounds, a gap that was also verified in the artistic literature. Testing was therefore carried out to determine the influence of amplification on the audibility of the softer main components of the sounds. It consisted in recording with close microphone placement a sample of guitarists playing on their guitars a set of takes of the lowest string lightly touched at a myriad of established locations, and left to vibrate. The recordings were then spectrally analysed and the data was treated and evaluated taking psychoacoustics into account. The results show that the amplification with close microphone placement of sounds of guitar multiphonics introduces novelty to an audience relatively to the non-amplified instrument, regardless of room size. The results and assumptions based thereon were implemented in a piece for amplified guitar and live electronics, and in a guitar piece for which artistic research was carried out, leading to a new form of multiphonics usage.